Triadic Interactions in Families of Adolescents with Anorexia Nervosa and Families of Adolescents with Internalizing Disorders - Balottin, Laura; Mannarini, Stefania; Mensi, Martina M.; Chiappedi, Matteo; Gatta, Michela (Frontiers in Psychology, 2017)
The latest studies and practice guidelines for the treatment of adolescent patients with anorexia nervosa agree in pointing out the key role played by parents in determining the young patients’ therapeutic possibilities and outcomes. Still family functioning has usually been studied using only self-reported instruments. The aim of the present study is therefore to investigate the triadic interactions within the families of adolescents with anorexia nervosa using a semi-standardized observational tool based on a recorded play session, the Lausanne Trilogue Play (LTP). Parents and adolescent daughters, consecutively referred to adolescent neuropsychiatric services, participated in the study and underwent the observational procedure (LTP). The 20 families of adolescent girls with anorexia nervosa (restricting type) were compared with 20 families of patients with internalizing disorders (anxiety and depression). The results showed different interactive patterns in the families of adolescents with anorexia nervosa: they had greater difficulties in respecting roles during the play, maintaining the joint attention and in sharing positive affect, especially in the three-together phase (third phase). The majority of these families (12) exhibited collusive alliances. The parental subsystem appeared frequently unable to maintain a structuring role, i.e., providing help, support and guidance to the daughters, while the girls in turn often found it hard to show independent ideas and develop personal projects. Parents experienced difficulty in carving out a couple-specific relational space, from which the ill daughter was at least temporarily excluded also when they were asked to continue to interact with each other, letting the daughter be simply present in a third-part position (fourth phase). The study of the triadic interactions in the families of adolescents with anorexia nervosa may help to shift the attention from the exclusive mother–daughter relation to the involvement of the father, and of the parental couple as a whole. The family functioning is in fact well established as a maintaining factor of anorexia nervosa or vice versa as a facilitating factor in the therapeutic process.